PENERAPAN MODEL PEMBELAJARAN PJBL UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMBELAJARAN MATEMATIKA MATERI MEMBANDINGKAN DAN MENGURUTKAN BILANGAN CACAH - Dian Ristyawati (LPPM Universitas Bina Bangsa, 2023)
Improving the learning outcomes of Class 1A students of SDN 2 Girimoyo in Mathematics subjects on sorting and comparing numbers 1-20 by using the PJBL learning model. The Classroom Action Research method is carried out collaboratively between researchers as learning innovators and learning implementers. Student learning outcomes improved. Both from the attitude and skill aspects. And summative learning outcomes or knowledge also increased, from Pre-Cycle the classical level of completeness was only 45% in Cycle I increased to 64% and in Cycle I increased to 82%. The use of the PJBL Learning model in Mathematics subjects on sorting and comparing small numbers 1-20 in Class 1A SDN 2 Girimoyo experienced a significant increase in completeness. Thus the PTK carried out can be declared successful in improving student learning outcomes